Exogenous cholesterol modulates oxidative stress and freezability of mithun spermatozoa - PERUMAL, P (The Indian Journal of Animal Sciences, 2019)
Effect of cholesterol loaded cyclodextrin (CLC) on improvement of semen quality parameters (SQPs) and deduction of oxidative stresses following cryopreservation in mithun was explored. Total 50 ejaculates were selected out of 105 collected based on preliminary SQPs. Sperm was treated with 1 mg (Gr II) and 2 mg (Gr III) of CLC/ 120Ã—106 spermatozoa and without CLC served as control (Gr I). Diluted semen samples were cryopreserved at ultralow temperature. Frozen thawed samples were evaluated for motility (progressive forward [FPM]; in bovine cervical mucus penetration test [BCMPT] and in computer assisted sperm analyzer [CASA]), viability, total sperm and nuclear abnormality, intactness of plasma membrane and acrosome, intracellular enzymatic leakage and oxidative profile (Malondialdehyde; MDA). Result revealed a significant improvement in motility (FPM, BCMPT and CASA), viability, acrosomal integrity, cholesterol content and reduction of sperm and nuclear abnormalities, leakage of intracellular enzymes and oxidative stressors in 1 mg CLC treated group as compared to control. Moreover, intactness of acrosome and biochemical membrane was protected significantly in extender containing 1 mg CLC. Hence inclusion of mithun spermatozoa with CLC (1 mg/120Ã—106) prior to freezing improved the survivability in cryopreservation. The results clearly indicated the beneficial effects of CLC supplementation on freezability by reducing cryodamage and protecting the spermatozoa integrity.